The Implementation of Corpus-aided Discovery Learning in English Grammar Pedagogy - Yanto, Elih Sutisna; Nugraha, Sidik Indra (Journal of ELT Research, 2017)
The present study presents the instructional procedures of the implementation of corpus-aided discovery learning and the extent to which corpus-aided discovery learning can create motivating and successful English grammar learning environment for EFL (English as a Foreign Language) students. Corpora promotes inductive learning in terms of that students not only acquire grammar by language data, observation and self-discovery of rules, but also find it entertaining and exciting to make grammar rule generalization on their own (Cheng, 2011; Hunston,2002). Drawing on data of a questionnaire and an interview, the students recounted that incorporating corpus-informed data into grammar learning was very satisfying and useful, and students can be sure that the language they are practicing is up-to-date, used in everyday situations. It is not artificial or invented language but consists of the most widely used grammar (McCarthy, 2004). In addition, language corpora helped students to learn about certain language uses that were not available in any of the traditional tools. Another finding shows that students understood how certain language forms were used by native speakers of English, and students revealed more positive attitude toward corpus in learning English grammar. The findings imply that corpus-informed data can be a means of encouraging autonomous learning, illustrating real uses of abstract rules, presenting authentic daily grammar, and promoting exploratory inductive learning. However, some students, especially inexperienced students, found learning grammar through corpus-informed data was difficult or boring.